Macromolecules as targeted drugs delivery vehicles: an overview - Ali, Yousaf; Ali, Alqudah; Ahmad, Sadiq; Abd Hamid, Shafida; Farooq, Umar (Taylor & Francis, 2019)
Targeted drug delivery system improves the efficiency and safety of the therapeutic agents by managing the pharmacokinetics and pharmacodynamics of drugs. Currently, numerous drug carrier systems have been developed with different sizes, architectures and characteristics surface properties. Among different systems, macromolecules have a wide range of applications in targeted drug delivery system. The optimal drug loading potential, smooth drug releasing ability and biocompatibility are the distinguishing features that ensure the drugs delivery ability of macromolecules. This review briefly introduces some of the most commonly studied macromolecules which have been recommended as drugs delivery vehicles.